P225 Revised Bts Guidelines For Securing Cancer Diagnosis At Bronchoscopy – A Higher Recommended Yield Is Realistic And Achievable. (10th November 2014) - Stanton, AE; Mackinlay, CI
Abstract : Introduction: The recently updated BTS guidelines 1 on bronchoscopy recommend that a diagnostic level of 85% should be attainable when definite endobronchial tumour is visible, an increase from previous recommendation of 80%. We investigated whether this higher level was achievable. Methods: All patients undergoing bronchoscopy for suspected lung cancer were prospectively entered into a departmental database from April 2010, with performance analysed annually. The following specific data were entered: level of tumour presence (none seen / possible / definite tumour); diagnostic specimens taken (biopsy, brush, wash, TBNA); result of each diagnostic specimen (tumour present / not present, with reports "suspicious or suggestive" of tumour classified as "not present" unless there was a specific MDT decision to give a cancer diagnosis), and whether bronchoscopy was diagnostic of lung cancer overall. Finally clinical records were reviewed in patients without a bronchoscopic diagnosis of cancer to determine their final diagnosis. Results: In the 4 full years since commencement of data collection, 356 bronchoscopies were performed for suspected lung cancer, with confirmed cancer diagnosis in 301. Table 1 summarises diagnostic sensitivity for endobronchial biopsy, brush, wash and overall sensitivity for lung cancer diagnosis at bronchoscopy in patients with bronchoscopically definite tumour seen. In 3/4 years our overall diagnostic sensitivity has reached the level recommended (86.4–91.7%), with first year performance just below the new standard (84.4%). Conclusions: The revised level of recommended diagnostic rate at bronchoscopy for definite tumour appears to be realistic and achievable. This should remain as the standard of care for patients undergoing bronchoscopy for suspected lung cancer. Reference: BTS Guideline for diagnostic flexible bronchoscopy in adults. Thorax 2013;68(Suppl 1)